Transition-metal-free glucose-derived carbonaceous catalyst catalyzes direct C-H arylation of unactivated arenes with aryl halides - Jori, Popat K.; Jadhav, Vrushali H. (ChemistrySelect, 2019)
Transition metal free coupling reactions have gained lot of importance recently. The traditional method for the synthesis of biaryl's uses organometallic reagents for the arylation reactions. There are certain drawbacks associated with such traditional methods. Use of expensive metals, metal impurities in the products formed and disposal of metal waste generated are major problems that need to be taken care of. Thus, research has been focussed on using transition metal free catalyst for cross coupling reactions to encourage green environment and it still remains a challenge for researchers. Carbonaceous catalyst have attracted great attention recently as a heterogeneous catalyst as it has a carbon skeleton that is stable, easily separable, reusable, eco-friendly and highly economical compared to other heterogeneous catalyst. Carbonaceous catalysts have been studied in variety of organic reactions such as hydrolysis, dehydration, esterification, alkylation, condensation, oxathioketalization, dimerization, benzylation and trimethylsilylation, etc. It was estimated that - stacking interactions between carbonaceous catalyst and arenes will accelerate the coupling reaction. However to the best of our knowledge, there are no reports available in literature on use of carbonaceous catalyst for direct arylation of arenes. And thus, we developed a new method for C-H arylation of unactivated arenes with aryl halides using a transition metal free D-glucose derived carbonaceous catalyst.
Keywords: Arylation; carbonaceous; glucose; metal-free